PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MENJELAJAH KEBERAGAMAN BERBANTUAN PROBLEM BASED LEARNING KELAS IV SD - Muliani Rahayu, Dina; Astuti, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education has an important role in preparing a quality generation. The use of interactive learning media is needed in the teaching and learning process to improve the quality of education. This research aims to develop interactive learning media in the form of comic strips assisted by Problem Based Learning (PBL) for grade IV elementary school students, describe the feasibility of the media, and evaluate its impact on student learning outcomes in Pancasila Education lessons. The method in this study uses Research & Development (R&D) by following the eight steps of Borg and Gall (1981:792). Data were collected through pretest and posttest, observation, interviews, and questionnaires. The results of the study show that the comic entitled